Pekerja Pers Menjelang Senja Kala Media Cetak - Mukhijab Mukhijab (Jurnal Community, 2018)
This article describes the dynamics of the media industry, particularly the print media industry. The growing effect of information technology that gave birth to online media in the form of online media and social media has encouraged consumers and readers to turn away from the print media. The next effect, media producers and services reduces the portion of advertising spending in print. There was a tempestuous print media business. Some print media closed their businesses. Media workers as part of the editorial division as well as non-editorial employees bear the brunt of the bankruptcy of media companies. This paper is limited to describe objectively how the situation of media workers at dusk when print media.Keywords: media industry, information technology, print media